2016
DOI: 10.5539/ibr.v9n5p180
|View full text |Cite
|
Sign up to set email alerts
|

Grocery Retailing in India: Online Mode versus Retail Store Purchase

Abstract: E-retailing is entering into the Indian retail scenario in a noticeable way and online grocery retailing holds a promise of acceptance by the Indian customers. This paper attempts to discover the market potential of online grocery retailing in India and consumers' perception towards its different aspects. Confirmatory factor analysis proposes that there are five underlying dimensions (convenience, value for money, variety, loyalty and ambient factors) governing the selection of mode for grocery purchase. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…These results contribute to future research and academia by enhancing the understanding of e-loyalty, specifically in the context of online grocery shopping. Third, the present study validates findings of previous studies (Anusha Sreeram et al, 2017;Dawes & Nenycz-Thiel, 2014;Droogenbroeck & Hove, 2017;Hansen, 2006;Huyghe et al, 2016;Morganosky & Cude, 2000;Narayan & Chandra, 2015;Rafiq et al, 2013;Siddiqui & Tripathi, 2016;Yan Huang & Harmen Oppewal, 2006) regarding the differing nature of online grocery shopping to other forms of online stores. In all, the three contributions fulfill the literature and theoretical gap.…”
Section: Indirect Effectsupporting
confidence: 90%
See 2 more Smart Citations
“…These results contribute to future research and academia by enhancing the understanding of e-loyalty, specifically in the context of online grocery shopping. Third, the present study validates findings of previous studies (Anusha Sreeram et al, 2017;Dawes & Nenycz-Thiel, 2014;Droogenbroeck & Hove, 2017;Hansen, 2006;Huyghe et al, 2016;Morganosky & Cude, 2000;Narayan & Chandra, 2015;Rafiq et al, 2013;Siddiqui & Tripathi, 2016;Yan Huang & Harmen Oppewal, 2006) regarding the differing nature of online grocery shopping to other forms of online stores. In all, the three contributions fulfill the literature and theoretical gap.…”
Section: Indirect Effectsupporting
confidence: 90%
“…Knowledge in the area of e-loyalty in relation to online grocery shopping remains less explored and provides a strong case for ongoing research. Initial work has laid the foundation for the development of holistic models (Anesbury et al, 2016;Nenycz-Thiel et al, 2016;Siddiqui & Tripathi, 2016;Sreeram et al, 2017). However, there are many limitations in understanding the concept of loyalty in online grocery shopping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through two mediators-advertising characteristics and customer attitude-the indirect relationship between online and conventional advertising and consumer purchasing behaviour is assessed in order to identify key variables that significantly affect consumer purchasing behaviour. Results showed that brand loyalty, advertisement quality, design, content, customer purchasing history, and advertisement Siddiqui & Tripathi (2016) in their study suggested that Online grocery shopping offers the promise of being accepted by Indian consumers as e-retailing makes a noticeable entry into the Indian retail landscape. This essay makes an effort to ascertain the market potential for online grocery retailing in India as well as consumers' attitudes regarding its various facets.…”
Section: Major E-grocery Playersmentioning
confidence: 91%
“…Many studies have been conducted to understand the determinants of consumer purchase intention toward online grocery shopping among different demographics (e.g., [22,23]), or in different countries, for example, China [24,25], India [26], Germany [27], Korea [28], Malaysia [29], Netherlands [30], Pakistan [31], Portugal [32], Thailand [33], U.K. [34], U.S. [35], and Vietnam [36].…”
Section: E-commerce Grocery Shopper Behaviormentioning
confidence: 99%